The impact of newborn screening on cystic fibrosis testing in Victoria, Australia. Issue 7 (July 1995) - Balnaves, M E; Bonacquisto, L; Francis, I; Glazner, J; Forrest, S
Abstract : Newborn screening for cystic fibrosis (CF) by examining the levels of immunoreactive trypsinogen was introduced in Victoria in 1989. This was modified by the addition of testing for the common CF gene mutation, delta F508, in 1990. Problems with the first newborn screening protocol were overcome with the addition of the DNA test as there was no need to contact the majority of families, there was a reduced number of sweat tests, and less anxiety was experienced by parents. The mode of diagnosis changed from failure to thrive, steatorrhoea, rectal prolapse, and family history to diagnosis through newborn screening. Newborn screening dramatically reduced the time of diagnosis of CF to approximately six weeks or less in the majority of cases. Since the introduction of newborn screening, the uptake of prenatal diagnosis in CF families has increased two and a quarter fold.